Government incentives for technological learning in Korea - Kim, Jang Saeng (KDI School, 2011)
Technological progress is a key determinant of economic growth. As many scholars pointed out, it is one of the key measures that can analyze and explain success or failure of a country’s economic development. This study addresses three issues as such: 1) what government incentives have been initiated, 2) how market (firms) has responded to government incentives, 3) what interactive framework between the two has played to achieve technological learning from 1960s to 1990s. The study defines a framework of government incentives for technological learning on the basis of outward-looking development strategy as follows: 1) industrial policy as a demand of technology, 2) science and technology policy as a supply of technology. Tax exemptions and financial support are practical examples of incentives to stimulate economic units. For the market responses to the government incentives, the study introduces firms’ continuous innovation for serving best goods and services with low cost to satisfy customers. The framework covers the following items based on firms’ devotion for acquiring knowledge and intensity of efforts: 1) technology transfer and diffusion, 2) in-house R&D, 3) human capital, and 4) crisis management and organizational restructuring within firm. As a conclusion, this study provides following implications for catching-up countries based on Korea’s experience; 1) applied technology development policy tends to foster faster economic growth than that of basic scientific research oriented policy in the early stage of industrialization (the role of KIST and its spin-offs), 2) interactive linkage between government and market is essential (a case of semiconductor and CDMA industrial consortiums), 3) government incentive with high pressure to stimulate market should be sustainable in the early stage of development (monthly export promotion meeting as a platform of trouble shooting). In addition, the study points out common elements to develop technology as such: government leadership, appropriate strategy and commitment, welltrained manpower, effective technology supporting systems, attractive incentive mechanism, and intensifying efforts of business anchors.
Thesis(Master) --KDI School:Master of Public Policy,2011